Surface roughness and wear behavior of occlusal splint materials made of contemporary and high-performance polymers - Benli, Merve; Gumus, Beril Eker; Kahraman, Yusuf; Gokcen-Rohlig, Bilge; Evlioglu, Gulumser; Huck, Olivier; Ozcan, Mutlu (SPRINGER, 2020)
With the development of a digital technology of computer-assisted manufacturing (CAD/CAM) and new age materials, the use of new types of occlusal splint is to consider. The aim of the present study was to evaluate the surface roughness (Ra) and wear behavior of different CAD/CAM materials against enamel antagonist through a simulated chewing test. A total of 75 specimens made from ethylene vinyl acetate (EVA), polymethyl methacrylate (PMMA), polycarbonate (PC), polyetheretherketone (PEEK), and polyethyleneterephthalate (PETG) as a control were polished to evaluate the Ra before loading by optical profilometry and further analyzed by scanning electron microscopy (SEM). Specimens of each group were subjected to thermomechanical fatigue loading in a chewing simulator (60000 cycles at 49 N with 5-55 degrees C thermocycling). The wear volume loss and change in Ra of each specimen after the simulated chewing were analyzed. One-way ANOVA, paired samples t test, and Pearson correlation analysis were performed for statistical analyzes. The result showed that the volume loss and Ra varied among the materials tested. EVA exhibited the greatest amount of Ra and volume loss (p 0.05). SEM investigations revealed different wear behaviors, especially in EVA. As PEEK showed significantly more favorable results, PEEK splints should be considered as a new therapeutic option for occlusal splint.
Keywords: Occlusal splint; PEEK; Wear; Surface roughness; EVA; ORAL APPLIANCES; IN-VITRO; CAD/CAM; FABRICATION; MANAGEMENT; POLYETHERETHERKETONE; ANTAGONIST; RESISTANCE; STRENGTH; DESIGN; Dentistry, Oral Surgery & Medicine